A novel role for C3 in antibody-induced red blood cell clearance and antigen modulation - Girard-Pierce, Kathryn R. (American Society of Hematology, 2013)
Hemolytic transfusion reactions (HTRs) due to incompatible red blood cell (RBC) transfusions are a leading cause of transfusion associated death. Although many transfused incompatible RBCs are cleared, some remain in circulation despite the presence of RBC-specific antibodies, potentially due to “antigen modulation.” With a goal of better understanding incompatible RBC clearance, we generated a murine model with RBC-specific expression of a clinically significant human antigen (KEL2) known to be involved in antigen modulation as well as in HTRs. Wild-type (WT) recipients transfused with transgenic KEL2 RBCs generated anti-KEL glycoprotein alloantibodies, which fixed complement, led to intravascular hemolysis, and resulted in decreased levels of KEL2 antigen detectable on cells remaining in circulation. Antigen modulation did not appear to solely reflect removal of RBCs with higher antigen expression, because cells continued to display antigen modulation in the absence of significant clearance. Recipients genetically lacking complement exhibited lesser degrees of incompatible RBC clearance and antigen modulation in comparison with WT or FcγR knock-out (KO) animals, suggesting a role for complement in RBC clearance. In summary, this HTR model may serve as a platform to test strategies to downmodulate antigen and inhibit incompatible RBC clearance, thus potentially mitigating transfusion dangers.